2022
DOI: 10.3390/v14102296
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Pattern Comparisons of the SARS-CoV-2 Delta Variant in Countries/Regions with High and Low Vaccine Coverage

Abstract: It has been argued that vaccine-breakthrough infections of SARS-CoV-2 would likely accelerate the emergence of novel variants with immune evasion. This study explored the evolutionary patterns of the Delta variant in countries/regions with relatively high and low vaccine coverage based on large-scale sequences. Our results showed that (i) the sequences were grouped into two clusters (L and R); the R cluster was dominant, its proportion increased over time and was higher in the high-vaccine-coverage areas; (ii)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…The C to U bias was also found in other variants of SARS-CoV-2 [ 16 , 26 ]. It was revealed that the proportion of the C to U transition for the Delta variant in different regions was about 36% [ 16 ]. However, we found that its proportion for Omicron in Oceania and Asia was also approximately 36%, but in North America, South America, and Europe, the proportions exceeded 41%, and in Africa it was only 32%.…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…The C to U bias was also found in other variants of SARS-CoV-2 [ 16 , 26 ]. It was revealed that the proportion of the C to U transition for the Delta variant in different regions was about 36% [ 16 ]. However, we found that its proportion for Omicron in Oceania and Asia was also approximately 36%, but in North America, South America, and Europe, the proportions exceeded 41%, and in Africa it was only 32%.…”
Section: Discussionmentioning
confidence: 73%
“…The tendency of mutation biases and context preferences suggested the contribution of the APOBEC, as APOBEC cytosine deaminase enzyme could cause transition of C to U [25]. The C to U bias was also found in other variants of SARS-CoV-2 [16,26]. It was revealed that the proportion of the C to U transition for the Delta variant in different regions was about 36% [16].…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations